S57 The Role of Vitamin D Deficiency in Regulating the Severity and Duration of Murine Lung Injury. (19th November 2012) - Lax, S; Parekh, D; Dancer, R; Thickett, D
Abstract : Introduction: Vitamin D has been shown to modulate both the innate and adaptive immune responses. Patients deficient have increased susceptibility to both infection and autoimmunity. Our research suggests patients with, or at risk of developing acute lung injury (ALI), are severely Vitamin D deficient/insufficient. As there are no licenced treatments for ALI, novel therapies need to be developed, therefore we investigated the effect of Vitamin D deficiency in a murine model of ALI to understand the mechanistic drivers of its action. Methods: Using a diet completely devoid of Vitamin D, we established near complete Vitamin D deficiency in otherwise wild type C57Bl/6 mice. We combined this with intra-tracheal instillations of LPS (50µg), and analysed the inflammatory response within the lungs of these mice compared to those fed on a Vitamin D sufficient diet. In addition, systemic Vitamin D supplementation was assessed by intra-peritoneal injection of cholecalciferol 48hrs prior to LPS instillation. Cell infiltrates, expression of several inflammatory markers within bronchial lavage fluid (BALF), as well as tissue permeability were examined to evaluate the immune response and resulting lung damage. Results: Dietary Vitamin D deficient mice (n=12) had elevated BALF protein concentration (p=0.0369) and red blood cell (RBC) extravasation (p=0.084) 48hrs post IT-LPS, suggestive of increased alveolar epithelial damage. BALF levels of VEGF (p=0.0023) and CXCL1/KC (p=0.0121) were significantly increased 48hrs post-LPS, indicating an increase in the inflammatory response in deficient mice. Moreover, inflammation was prolonged with both the total number of cells recruited into the BALF (p=0.0479), and the number of apoptotic neutrophils (p=0.034) significantly higher at 96hrs post LPS in Vitamin D deficient mice. Furthermore, wild type mice with normal Vitamin D levels pre-treated with cholecalciferol had reduced BALF cellular inflammation (p=0.0093), with a lower BALF protein concentration (p=0.076) and RBC accumulation in BALF (p=0.0274) 48hrs post-LPS. Conclusion: Our data indicate that Vitamin D deficiency significantly augments both the severity and duration of murine lung injury and that exogenous Vitamin D reduces lung responses to LPS even in mice with normal Vitamin D levels. These data support the use of Vitamin D to both prevent and potentially treat established ALI.